2015
DOI: 10.1371/journal.pone.0140950
|View full text |Cite
|
Sign up to set email alerts
|

A Design Pattern for Decentralised Decision Making

Abstract: The engineering of large-scale decentralised systems requires sound methodologies to guarantee the attainment of the desired macroscopic system-level behaviour given the microscopic individual-level implementation. While a general-purpose methodology is currently out of reach, specific solutions can be given to broad classes of problems by means of well-conceived design patterns. We propose a design pattern for collective decision making grounded on experimental/theoretical studies of the nest-site selection b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
132
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 115 publications
(132 citation statements)
references
References 54 publications
0
132
0
Order By: Relevance
“…Recently, Reina et al (2015b) studied a binary foraging scenario, where the objective of the swarm is to decide which foraging patch offers the highest quality resource and to forage from that patch. The environment is characterized by a central retrieval area and two foraging patches.…”
Section: Asymmetric Option Qualities and Costs: Antagonistic Casementioning
confidence: 99%
“…Recently, Reina et al (2015b) studied a binary foraging scenario, where the objective of the swarm is to decide which foraging patch offers the highest quality resource and to forage from that patch. The environment is characterized by a central retrieval area and two foraging patches.…”
Section: Asymmetric Option Qualities and Costs: Antagonistic Casementioning
confidence: 99%
“…It has previously been suggested that swarms should be understood as informationprocessing cognitive systems Reina et al 2015b). In contrast to traditional information-based approaches, the ICR framework characterises information flow not in terms of transfer entropy, but in terms of the information gain rate, i.…”
Section: The Icr Framework and Future Workmentioning
confidence: 99%
“…Because of this, it is not possible to use it for precisely predicting or optimising swarm performance, or to study macroscopic robot population dynamics, as can be done by using probabilistic finite state machines and differential equations (e.g. Liu and Winfield 2010;Montes de Oca et al 2011;Mather and Hsieh 2012;Reina et al 2015b;Scheidler et al 2016;Valentini et al 2016). Similarly, it is not possible to use the framework to uncover behaviour rules of agents, as can be done by using Turing Learning (Li et al 2016).…”
Section: The Icr Framework and Future Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The negative feedback by stop signals increases the reliability of the decision-making process because it solves the problem of deadlocks and triggers bistable distributions (cf. [31,32]). In [23] the authors investigated the role of positive/negative feedbacks in addition to noise in the emergence of self organization and collective decision-making.…”
Section: Related Workmentioning
confidence: 99%